Exploring the multifaceted roles of Sonneratia apetala and Nipa fruticans in coastal habitat restoration and bioactive properties discovery - Sabina Yasmine; Rezwana Zaman Proma; Md. Ripaj Uddin; Mohammad Saydur Rahman; Md. Hamedul Islam; Muhammad Abdullah Al Mansur; AHM Shofiul Islam Molla Jamal; Abu Yousuf; Md. Hasnain Mustak; Sarker Kamruzzaman; M. Mahboob Ali Siddiqi (Phytomedicine Plus)
Background: Sonneratia apetala and Nipa fruticans are mangrove species, perennial wild plants with significant therapeutic, ecological, and environmental value. They are extensively utilized by the local communities of the Sundarbans and coastal estuaries for various purposes. Aim of the study: This study aims to provide an in-depth review of these plants, relying on secondary data and information. Methods: Compile the secondary data from at least 50 relevant pieces of literature. Results: S. apetala fruits exhibit substantial antioxidant, antimicrobial, analgesic, antidiarrheal, and anti-diabetic properties. Additionally, the bark and leaves offer considerable therapeutic benefits. The plant contains various phytochemicals such as polyphenols include flavonoids, anthocyanins and alkaloids along with carbohydrates, proteins, fiber, minerals (such as Ca, K, Mg, S, Cu, Fe, Zn, Mn), and vitamins (including thiamine and riboflavin). Its leaf and fruit extracts show potential for applications in the food industry and green chemistry. The seed extract demonstrates the highest cytotoxic properties (LC50=36 μg/mL) among other parts of the plant, along with antibacterial effects and dose-dependent analgesic and antidiarrheal properties. The leaf and bark extracts exhibit significant antidiabetic potential, with IC50 values of 0.286±0.022 and 0.432±0.01 mg/mL respectively. The seeds are particularly rich in polyphenols (300.1 mg GAE/g), flavonoids (30.6 mg CE/g), anthocyanins (2.3 μmol/g), and vitamin C (4.0 mg/g), showcasing their strong antioxidant properties. The pericarp, though lower in these compounds, still presents significant nutritional value, containing 55.4 mg GAE/g polyphenols and 14.6 mg CE/g flavonoids. Nutritional analysis shows the pericarp's moisture content is 84.2 %, along with high carbohydrates (29.6 %) and proteins (8.8 %), while the seed has 55.6 % moisture and 11.5 % proteins. Nipa fruticans presents lucrative findings, including vinegar production, low-fat biscuits with high nutrient values, bioethanol, among others. Various parts of this plant contain essential elements in significant amounts and only trace amounts of heavy metals, indicating its safety for medicinal purposes. Conclusion: The phytochemical, nutritional, and elemental analyses of these plants highlight its potential health benefits, food value and significance in research. This comprehensive analysis underscores S. apetala's and N. fruticans broad nutritional and phytochemical significance, making it a valuable subject in studies of natural products and human health.